Pengaruh Good Corporate Governance dan Pengelolaan Manajemen Risiko Terhadap Reputasi Dengan Kinerja Keuangan Sebagai Variabel Intervening di Bank Central Asia Syariah - Kholifah Ragil Saputra; Lu’lu’il Maknuun; Ahmad Mukhlisuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aimed to find out whether Good Corporate Governance and Risk Management affected reputation with financial performance as an intervening variable in the case study of Bank Central Asia Syariah. In addition, this study also aimed to test whether financial performance variables mediatd the relationship between each variables. The sample used in this research was Bank Central Asia Syariah's quarterly and annual reports published for 2017-2022. The method used was a quantitative approach with data analysis using smartPLS, the data used was secondary data. The research results showed that Good Corporate Governance has significant effect on reputation.Good Corporate Governance has not is proven significant to financial performance. Risk management has proven to have a significant effect on reputation. Risk management has a significant effect with a negative influence on financial performance. Financial performance has proven to have a significant effect on reputation. The path test showed that financial performance is unable to mediated Good Corporate Governanceon and risk management on reputation. Keywords: GCG, Risk Management, Reputation, Financial Performance